2021
DOI: 10.1038/s41598-021-02968-8
|View full text |Cite
|
Sign up to set email alerts
|

A geostatistical approach to estimating source apportionment in urban and peri-urban soils using the Czech Republic as an example

Abstract: Unhealthy soils in peri-urban and urban areas expose individuals to potentially toxic elements (PTEs), which have a significant influence on the health of children and adults. Hundred and fifteen (n = 115) soil samples were collected from the district of Frydek Mistek at a depth of 0–20 cm and measured for PTEs content using Inductively coupled plasma—optical emission spectroscopy. The Pearson correlation matrix of the eleven relevant cross-correlations suggested that the interaction between the metal(loids) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Font et al (2022) identified stainless-steel processes as one of the main contributors to Ni concentrations in an industrial area in the United Kingdom [ 71 ]. Although most literature suggests that Fe is of geogenic origin, steel production facilities were also identified as contributors to Fe concentrations mainly due to the blast furnaces' operation [ 72 , 73 ]. An extensive study on topsoil quality assessment near a closed steel smelter at the Capital Iron and Steel Factory, Beijing in China, confirmed that higher concentrations of Cu in soils surrounding the steelmaking site are mainly associated with steel smelting activities [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Font et al (2022) identified stainless-steel processes as one of the main contributors to Ni concentrations in an industrial area in the United Kingdom [ 71 ]. Although most literature suggests that Fe is of geogenic origin, steel production facilities were also identified as contributors to Fe concentrations mainly due to the blast furnaces' operation [ 72 , 73 ]. An extensive study on topsoil quality assessment near a closed steel smelter at the Capital Iron and Steel Factory, Beijing in China, confirmed that higher concentrations of Cu in soils surrounding the steelmaking site are mainly associated with steel smelting activities [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, there are only a few qualitative and quantitative studies being carried out on heavy metal apportionment in sources when compared to HMC, risk assessment or soil remediation (Jiang et al, 2017). Previously heavy metal source apportionment studies were utilized by geographic information systems‐based geostatistical models (Agyeman et al, 2021; Duan et al, 2020; Lv, 2019), multivariate statistics analyses (Qu et al, 2013) and isotopic signatures (Zhu et al, 2017) mostly as qualitative methods. However, the combination of geographic information system (GIS) with geostatistical and multivariate statistical analysis techniques has increasingly become useful in analysing the regional‐scale arrangement of the HMC within water and soil samples (Kattel et al, 2023; Ma et al, 2018; Zeng et al, 2022; Zhang & Zhang, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…[4,8,10]. To determine the source identifications and the spatial variations of heavy metals in soils, multivariate statistics are implemented in combination with geostatistical techniques [11,12]. There are also many receptor models which are used to identify the sources of heavy metals.…”
Section: Introductionmentioning
confidence: 99%